Investigating the role of chlorogenic acids and coffee type in coffee-induced teeth discoloration - Soyeon Kim; Shin Hye Chung; Ryan Jin Young Kim; Young-Seok Park (Acta Odontologica Scandinavica)
Objective: Coffee is one of the most popular beverages in the world, with millions of people consuming it every day. The effect of coffee on teeth discoloration has long been a concern for both coffee drinkers and dental professionals. To address this concern, this study aimed to investigate the role of chlorogenic acids (CGAs) and the type of coffee in coffee-induced teeth discoloration.